2012
DOI: 10.1002/pmic.201270086
|View full text |Cite
|
Sign up to set email alerts
|

New and improved proteomics technologies for understanding complex biological systems: Addressing a grand challenge in the life sciences

Abstract: This White Paper sets out a Life Sciences Grand Challenge for Proteomics Technologies to enhance our understanding of complex biological systems, link genomes with phenotypes, and bring broad benefits to the biosciences and the US economy. The paper is based on a workshop hosted by the National Institute of Standards and Technology (NIST) in Gaithersburg, MD, 14–15 February 2011, with participants from many federal R&D agencies and research communities, under the aegis of the US National Science and Technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 25 publications
(24 reference statements)
0
46
0
Order By: Relevance
“…They then engineered five protein constructs bearing different mutations and rearrangements, and demonstrated that these constructs could be discriminated with accuracies ranging from 86 to 99%. Protein sequencing will allow studies of complex interactions among cells in different tissues [68]. …”
Section: Discussionmentioning
confidence: 99%
“…They then engineered five protein constructs bearing different mutations and rearrangements, and demonstrated that these constructs could be discriminated with accuracies ranging from 86 to 99%. Protein sequencing will allow studies of complex interactions among cells in different tissues [68]. …”
Section: Discussionmentioning
confidence: 99%
“…The high-throughput technical advances that have ensued through the past decade permit the global and focussed capture of dynamic changes in complex proteomes in a quantitative manner. The coming of age of quantitative proteomic methodologies, together with increasing awareness of the pre-analytical and analytical variables that confound data interpretation, have ensured that modern proteomic applications are increasingly offering a viable route to delivering robust, reproducible and standardised data sets [31,32]. The differential and quantitative profiling of the dynamic protein changes in health and disease will inevitably further our understanding of the mechanistic basis of disease.…”
Section: Proteomics In Drug Discoverymentioning
confidence: 99%
“…However, development of new diagnostic and therapeutic tools for CKD is hampered by our incomplete understanding of its underlying pathophysiology. In this direction, targeted mass spectrometry is a powerful tool, enabling simultaneous quantification of several prespecified proteins in biologic samples (Hood et al, 2012). Determining the abundance of protein components or targets of a given pathway using quantitative proteomics can generate a snapshot of the pathway status and activity within these samples.…”
Section: Introductionmentioning
confidence: 99%